Механізм злочинної поведінки - Бандурка, О. М.; Bandurka, O. M.; ORCID: http://orcid.org/0000-0002-0240-5517; Литвинов, О. М.; Lytvynov, O. M.; ORCID: http://orcid.org/0000-0003-2952-8258 (Вісник Кримінологічної асоціації України. - 2016. - № 3 (14). - С. 110-119, 2016)
Стаття присвячена аналізу закономірностей формування та функціонування елементів механізму злочинної поведінки. Останній розглядається як процес зміни зовнішнього середовища, складне психофізіологічне явище, в якому сконцентровані усі психічні і фізичні потенції індивіду.

A crime is a system, which is subordinated to the action of certain normalities. They are different in nature, the original foundations, dynamics of formation and functioning. Experiencing the influence from some factors of social environment, psychological substructures of personality, its motivational sphere, etc. They are dynamically transformed and affect other elements of the mechanism of criminal behavior. Therefore, their definition, description and analysis in the light of the mentioned mechanism are important applied tasks of criminological research. At a certain level of generalization, the mechanism of criminal behavior as an information model can be viewed and represented as a set of mental states and processes of activity, which form such a phenomenon as a crime. With regard to the specific of the raised problem, we should pay attention to strict correlation of mental states with the features of the processes of activity and so forth with the crime casus, and therefore, with those elements that are traditionally included in its information models – modus operandi, the perpetrator’s personality, the victim’s personality, the crime situation, etc. The mechanism is also defined as a system of bones (units), where the movement of one or more bones (leading) makes a definite movement of others. This definition, being extrapolated, also stresses on the need to establish correlation relations between the elements of the mechanism of criminal behavior. In this context, we can also consider the mechanism as the information model of a crime in the form of elements of a crime, where the features and properties of one or more elements determine the features and properties of other elements of the system. The mechanism of criminal behavior can also be defined as the mechanism of offender’s criminal conduct (i.e. his criminal behavior during the criminal event), as well as the collection of information about pre-criminal, criminal and post-criminal behavior of the offender. Accordingly, depending on the amount of information content we can distinguish the categories of the mechanism of criminal behavior in the narrow and broad sense. It is obvious that understanding the mechanism of criminal behavior in the broadest sense this category is the same with the category of “mechanism of offender’s behavior”. Considering the mentioned facts, the category of “mechanism of criminal behavior” can be defined as a system of information on socially dangerous acts determined by psycho-physiological characteristics of the offender’s personality, other objective and subjective factors.

Статья посвящена анализу закономерностей формирования и функционирования элементов механизма преступного поведения. Последний рассматривается как процесс изменения внешней среды, сложное психофизиологическое явление, в котором сконцентрированы все психические и физические потенции индивида.
Mechanism of criminal behavior
Механизм преступного поведения
Бандурка, О. М. Механізм злочинної поведінки / О. М.Бандурка, О. М. Литвинов // Вісник Кримінологічної асоціації України. - 2016. - № 3 (14). - С. 110-119.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; протидія злочинності; противодействие преступности; crime counteraction; механізм злочинної поведінки; mechanism of criminal behavior; механизм преступного поведения; злочинна поведінка; criminal behavior; преступное поведение